Not p-values, said a little bit differently - Richard Startz (Econometrics, 2019)
As a contribution toward the ongoing discussion about the use and mis-use of p-values, numerical examples are presented demonstrating that a p-value can, as a practical matter, give you a really different answer than the one that you want.
Keywords: C0; C4; 330; p-value; Bayesian